PENGARUH JUMLAH PERUSAHAAN, JUMLAH PENDUDUK, DAN PDRB TERHADAP PENERIMAAN PAJAK REKLAME DI PROVINSI DKI JAKARTA TAHUN 2004-2015 - Gusti Harmaji; Amelia Sandra (Jurnal Akuntansi, 2020)
One of the efforts made by the DKI Jakarta Province government in maximizing local revenue is by optimize local tax revenue, especially advertisement tax. Advertisement tax is one of most important and potential components of local taxes for DKI Jakarta Province. Advertisement tax is tax on implementation of advertisement. Variables used in this study are amount of companies, population and GDP as independent variables and advertisement tax revenue as dependent variable. The purpose of this study is to find out if there is any influence of three independent variables to dependent variable. Data completion in this study uses documentation technique by collecting data from related institution. Data used in this study are data from 2004-2015. Analysis technique used is multiple linear regression analysis using Microsoft Excel 2013 software. The results of this research show that amount of companies have a value of P-value of 0,013117, the value is smaller than 0,05 (< 0,05), population has a value of P-value of 0,031598, the value is smaller than 0,05 (<0,05), and GDP has a value of P-value of 0,000369, the value is smaller than 0,05 (<0,05). The conclusion of this research shows that there is sufficient evidence that amount of companies, population and GDP have a positive influence on advertisement tax revenue in DKI Jakarta Province. Keywords: amount of companies, population, GDP, advertisement tax revenue